2020
DOI: 10.1101/2020.05.11.20086439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus protective immunity is short-lasting

Abstract: In the current SARS-CoV-2 pandemic a key unsolved question is the quality and duration of acquired immunity in recovered individuals. This is crucial to solve, however SARS-CoV-2 has circulated for under five months, precluding a direct study. We therefore monitored 10 subjects over a time span of 35 years , providing a total of 2473 follow up person-months, and determined a) their antibody levels following infection by any of the four seasonal human coronaviruses, and b) the time period after which reinfectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 26 publications
3
92
0
Order By: Relevance
“…Accordingly, vaccine strategies against SARS-CoV-2 may need boosting to maintain sufficient neutralizing antibody titers over a long time [ 5 ]. Waning antibody titers and reinfections are known from various HCoVs mainly responsible for common colds [ 5 , 12 , 31 ]. Recently a well-documented case of an asymptomatic SARS-CoV-2 reinfection was reported [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, vaccine strategies against SARS-CoV-2 may need boosting to maintain sufficient neutralizing antibody titers over a long time [ 5 ]. Waning antibody titers and reinfections are known from various HCoVs mainly responsible for common colds [ 5 , 12 , 31 ]. Recently a well-documented case of an asymptomatic SARS-CoV-2 reinfection was reported [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the duration of the acquired immunity after a SARS-CoV-2 infection is unclear. However, based on experience with reinfections from other human coronaviruses, it remains yet open if the immunity is long-lasting [ 12 ]. Several studies reported a rapid decay of SARS-CoV-2 immunoglobulin G (IgG) in asymptomatic individuals [ 13 ] and mild COVID-19 cases [ 14 ] but, more surprisingly, also in hospitalized patients presenting with the full clinical spectrum of COVID-19 [ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence for preformed immunity against the novel coronavirus SARS-CoV-2 (13)(14)(15)(16)(17) . Reports on memory T cell response to the endemic coronaviruses are lacking, but since antibody titers appear short-lived and frequent re-infections cannot be excluded (19)(20)(21)(22) , it is probable that the endemic coronaviruses with low virulence do not create lasting immunity. This then begs the question, which pathogen can generate a memory T cell response cross reactive to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high sequence similarity, the endemic coronaviruses are likely inducers of the preexisting immunity. However, immunity to these coronaviruses appears short-lived as antibody titers return to baseline levels at 4-12 months after infection (19)(20)(21) . It can also not be excluded that re-infection with the same coronavirus type can occur within a single year (22) .…”
Section: Introductionmentioning
confidence: 99%
“…Information about the duration of antibody response to SARS-CoV-2 is limited; however, currently it is known that the immunity acquired is temporary. Recent research highlights that immune response and antibody protection after recovery may depend on the severity of the infection, in some cases this protection can last for as little as 12 weeks while in others, no antibody protection is observed [49] , [50] , [51] , [52] , [53] , [54] . To assess the influence of this behavior on disease spread, we set the feedback parameter at constant values in order to map possible scenarios especially those related to second waves of infection.…”
Section: Parameter Fitting By the Least-squares Methodsmentioning
confidence: 99%